Cookies : the best recipes for the perfect anytime treat - Vreeland, Vaughn (Ten Speed Press, an imprint of the Crown Publishing Group, a division of Penguin Random House LLC, 2025)
"Delight your friends and family (and yourself) with 100 delicious cookies from NYT Cooking. Dessert is sometimes seen as a bonus, but what could be more essential than delightful treats? From NYT Cooking and curated by recipe creator, video journalist, and YouTube personality Vaughn Vreeland, Cookies is the ultimate collection of treats-from classic recipes that taste like home, to flavor-packed bites that will become your new go-tos. When you need a trusted recipe for the Best Chocolate Chip or Classic Oatmeal Raisin Cookies, look no further. If you'd like something fresh, try the Salted Margarita Bars or Lemon-Turmeric Crinkle Cookies. Feeling a little nutty? Rum-Buttered Almond or Peanut Butter Miso Cookies might do the trick. And when you can't wait to break out the holiday cookie tin, Gochujang Caramel Cookies and Pistachio Pinwheels will have you feeling festive all year long. Featuring time-tested recipes and expert guidance from trusted writers Yossy Arefi, Melissa Clark, Dorie Greenspan, Eric Kim, Genevieve Ko, Yewande Komolafe, Samantha Seneviratne, Susan Spungen, Vaughn himself, and many others, Cookies will serve up delight and inspiration for any party, picnic, or regular Tuesday night. Because you deserve a cookie." -- ONIX annotation.